Perancangan Drilling Jig Fixture untuk Flange Drum Spinner di PT. Melu Bangun Wiweka - Meri Rahmi; Natasya Azizia Putri; Akbar Robiyana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2026)
The tire manufacturing process involves a critical building stage using a drum spinner machine, which requires a flange to connect the drum and frame at PT. Melu Bangun Wiweka experienced frequent misalignment issues due to the manual drilling of flange holes. To solve this, a drilling jig fixture was developed to ensure accurate hole placement. Made from SS400, a material known for its good machinability under manual conditions, the fixture measures 303 × 400 × 500 mm. Its implementation significantly reduced drilling time from 21.67 minutes to 8.17 minutes. The estimated manufacturing cost of the fixture is IDR 12,097,097. By using this fixture, the company can save approximately IDR 6,436,000 per month when producing 1,000 units. A cost analysis reveals that the (BEP) is reached at 1,879 units, with each unit priced at IDR 17,807. This innovation improves efficiency, ensures precision, and offers significant cost savings in the long term.